192k views
0 votes
Help on this one as well ii manged to get an answer but If you understand it or im wrong an you please explain ! thank you !!

Help on this one as well ii manged to get an answer but If you understand it or im-example-1

2 Answers

4 votes
x + 3 = 3(y + 2)/2 therefore x + 3 = (3y + 6)/2 2(x + 3) = 3y + 6 2x + 6 = 3y + 62x = 3y x = 3y/2 x/3 = y/2

ANSWER: y/2
Hope this helps! Have a nice day!
-Lion

User Ansuman Bal
by
6.5k points
3 votes
Almost got it!

x + 3 = 3(y + 2)/2 [Multiplied both sides by 3]
so x + 3 = (3y + 6)/2
2(x + 3) = 3y + 6 [Multiplied both sides by 2]
2x + 6 = 3y + 6
2x = 3y [Subtracted 6 from both sides]
x = 3y/2 [Divided both sides by 2]
x/3 = y/2 [Divided both sides by 3]

So you wrote y/3 instead of y/2
Hope this helped!
User Kevin Kokomani
by
5.8k points